Does health information affect lifestyle behaviours? The impact of a diabetes diagnosis. (December 2022) - Gaggero, Alessio; Gil, Joan; Jiménez-Rubio, Dolores; Zucchelli, Eugenio
Abstract: Despite an increasing interest in the effect of health information on health-behaviours, evidence on the causal impact of a diagnosis on lifestyle factors is still mixed and does not often account for long-term effects. We explore the role of health information in individual health-related decisions by identifying the causal impact of a type-2 diabetes diagnosis on body mass index (BMI) and lifestyle behaviours. We employ a fuzzy regression discontinuity design (RDD) exploiting the exogenous cut-off value in the diagnosis of type-2 diabetes provided by a biomarker (glycated haemoglobin) drawn from unique administrative longitudinal data from Spain. We find that following a type-2 diabetes diagnosis individuals appear to reduce their weight in the short-term. Differently from previous studies, we also provide evidence of statistically significant long-term impacts of a type-2 diabetes diagnosis on BMI up to three years from the diagnosis. We do not find perceivable effects of a type-2 diabetes diagnosis on quitting smoking or drinking. Overall, health information appears to have a sustained causal impact on weight reduction, a key lifestyle and risk factor among individuals with type-2 diabetes. Highlights: We explore the causal impact of a diabetes diagnosis on BMI and lifestyle behaviours. We use a regression discontinuity design and a biomarker as our running variable. Individuals reduce their weight in the short-term following a diabetes diagnosis. We identify long-term effects on weight up until three years since the diagnosis. We do not find perceivable effects of a diagnosis on smoking or drinking.